Situation of Occupational and Environmental Health in Mexico - Martha Edilia Palacios Nava; Ana Rosa Moreno Sánchez; María del Pilar Paz Román; Juan José García García; Rodolfo Nava Hernández (Ubiquity Press, 2018)
Background: Mexico has a great diversity and richness of natural resources, but evaluations of the quality of life of Mexicans show the deep inequalities and the gap between rich and poor. While 5% of families concentrate 58% of the wealth, the health spending in environment and health is 0.2 and 2.7 of the GDP respectively. This has repercussions both on the gradual deterioration of the environment and on the insufficient health and social security coverage of the working population. Objective: To describe the current situation of occupational and environmental health in Mexico. Methods: A bibliographic review was performed on the socioeconomic, demographic, environmental, legal and health status of the Economically Active Population (EAP). Findings: There is a constant deterioration of terrestrial and marine ecosystems, accompanied by an increase in environmental pollution in large cities. The unemployment rate of the EAP has decreased in one year to 3.4%, but the informal labor rate reached 57.3%, which translates into population without social security. Compliance with legislation for the protection of workers' health is insufficient. The recent amendments to the law have meant a setback in these respects. The reported information on accidents and occupational diseases corresponds to only 34% of workers. There has been a decrease in the rate of work accidents in the last six years, but an increase in diseases and permanent disabilities. During 2016, the first cause of occupational illness was hearing loss, but the profile was dominated by musculoskeletal diseases, which together reached 36.5%. Conclusions: To improve the occupational and environmental health situation, it is necessary to implement general and particular measures against inequalities, increase the budget in health and environment, enforce legislation and expand social security coverage to the population. These measures should be part of public policies as well as actions of academics and researchers.